Molecular Interaction Analysis of COX-2 against Curcuminoid and Xanthorizol Ligand as Anti Breast Cancer using Molecular Docking - Ridho Pratama; Laksmi Ambarsari; Tony Ibnu Sumaryada (IPB University, 2015)
Breast cancer is one of the most common cancer in the world that occurs in women. Thedevelopment process of cancer is regulated by a variety of pathways that involve various enzymes. COX-2 is an enzyme involved in the inflammatory process in further stages that will play importantroles in breast cancer cells progression. The uses of natural compound from plants give new hope forbreast cancer treatment with minimal side effects. Temulawak is a potential breast cancer drugs because it contains curcuminoid and xanthorizol. Curcumin and xanthorizol has been reported to have chemopreventive effect on colon cancer development. The drug that has same functions of these compounds needed to be examined with various approaches. One of the approach used in this research is molecular docking. Based on ligand analysis with Lipinski and toxicity test using ADMET, curcuminoid and xanthorizol met criteria as medicinal compounds. Curcumin had the highest binding affinity(?G) with the value -9.3 kcal/mol but still under commercial drug celecoxib binding affinity (?G) = -12,5. There were three hydrogen bonds in amino acid Arg106 and Tyr341 His75 which were amino acids in the active side of COX-2. There were 15 amino acids that have similar ties with commercial drug celecoxib. Based on the binding affinity and binding similiarity, curcuminoid and xanthorizol were predicted as compounds that have potential as competitive inhibitor of COX-2 enzyme.